Atmospheric deposition of polychlorinated biphenyls to seasonal surface snow at four glacier sites on Svalbard, 2013–2014. (March 2020) - Hermanson, Mark H.; Isaksson, Elisabeth; Divine, Dmitry; Teixeira, Camilla; Muir, Derek C.G.
Abstract: During spring 2014 we collected annual surface snow from four glacial sites on Svalbard, an archipelago in the European Arctic. The sampling sites are 230 km apart from west to east, but are at varying elevations, affecting local atmospheric contaminant inputs. Samples were analyzed for 209 polychlorinated biphenyl (PCB) congeners. The western sites, Holtedahlfonna and Kongsvegen, had the highest ∑PCB flux (26.7 pg cm −2 yr −1 at Kongsvegen) while the lowest was at Lomonosovfonna, in central Svalbard (14.4 pg cm −2 yr −1 ). The greatest difference between sites was the trichlorobiphenyl homologue which was nearly four times greater at Kongsvegen than the eastern site at Austfonna. The most concentrated congeners at each site were PCB-52, 70 + 74, 95, 101, 110 comprising 32–39% of ∑PCB, similar to Clophen 40 which is comprised 27% of these congeners. Similar variance of these congeners in samples and Clophen 40 was verified by principal components analysis. Air mass back trajectories from likely source areas for all sites were similar, indicating no difference in frequency or distribution of PCB from long-distances, suggesting local PCB sources contributing to Kongsvegen. We found 2, 3-DiCB (PCB-5) and 3, 3′-DiCB (PCB-11) at all sites; neither was found in western commercial PCB mixtures. PCB-5 may be from the Russian PCB product "Trichlorobiphenyl" or is residue from production of pigment violet 23. PCB-11 may come from waste incineration in northern Europe containing various pigments. These results, in comparison to earlier data from Lomonosovfonna, suggest that PCB inputs are variable and are not declining over time. Highlights: Clophen 40 contributes to PCBs on Svalbard. Local sites may be PCB sources to Svalbard glaciers. Use of 209 PCB congener analysis is necessary at remote sites. Winter PCB accumulation quantities are variable on Svalbard.